Discrete elemental analysis on the effect of particle morphology and size on interparticle contact force - Yongfeng Zhu; Wei Xiong; Wen Fan (PLoS ONE, 2025)
Particle morphology and size are fundamental characteristics that significantly influence the mechanical behavior of granular materials. This study introduces key parameters—aspect ratio (Ω), sphericity (S), and equivalent diameter (Dₑ)—into a modified Hertz-based contact model to conduct a multiscale study using contact mechanics theory and the discrete element method (DEM). A series of two-particle tests and triaxial compression simulations were performed. The results show strong agreement between numerical simulations and theoretical predictions at the particle scale, validating the modified contact model. At the sample scale, the peak deviatoric stress increased by approximately 15–40% as aspect ratio decreased from 1.00 to 0.33 and sphericity decreased from 1.00 to 0.11. Similarly, increasing the equivalent diameter from 3.78 mm to 8.82 mm led to a 20–35% rise in peak stress. At the particle scale, both normal and tangential contact forces increased with larger equivalent diameters but exhibited complex dependencies on morphology due to varied contact patterns. These findings enhance the understanding of how particle-scale characteristics influence macroscopic mechanical properties.